Pengembangan dan Evaluasi Usability Aplikasi Penjualan Rumah Berbasis Web terintegrasi Payment Gateway untuk Digitalisasi KPR In-House menggunakan Model Waterfall - Muhammad Patria; Mahardhika Dava Wardhana (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study develops a web-based home sales application to support In-House Mortgage (KPR In-House) financing at PT Nirwana Propertindo Sejahtera. The previous manual process led to administrative delays, limited transaction traceability, and a high risk of data loss. However, studies addressing an end-to-end digital KPR In-House system that integrates online applications, payment gateway–based installment payments, and standardized usability evaluation remain limited. The system was developed using the Waterfall model within the System Development Life Cycle (SDLC) and includes housing catalogs, installment simulation, online KPR applications, and integrated installment payments. Evaluation was conducted using Black Box Testing and the System Usability Scale (SUS). The results show that all system functions operate as expected and achieved a SUS score of 88.25, indicating high usability. The implementation improves transaction traceability, reduces the risk of document loss, and supports payment transparency. This study contributes an end-to-end digital KPR In-House process model, payment gateway integration, and empirical usability evidence.